COMPARATIVE AND LINGUOCULTURAL ANALYSIS OF THE CONCEPT "GENDER" IN UZBEK AND ENGLISH LANGUAGES - Zuparova Lobar Karimovna (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2024)
In the scientific description, the concept of gender is introduced in order to draw a line between the notion of gender and the social and cultural implications of the male-female concept: the division of roles, cultural traditions, the relationship of power in relation to the sex of people. The term gender is intended to exclude biological determinism, embodied in the concept of gender and ascribes all the sociocultural differences associated with gender, universal natural factors. Unlike the gender category, gender status and, accordingly, the gender hierarchy and gender-related behavioral models are not set by nature, but are "constructed" by the society (doing gender), prescribed by institutions of social control and cultural traditions. Gender relations are an important aspect of social organization. They express in a special way its system characteristics and structure the relations between speaking subjects.